UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SMP NEGERI KARYA MAKMUR DI MASA PANDEMI COVID-19 - Maryani Maryani (Jurnal Perspektif Pendidikan, 2020)
This study aims to (1) determine the principal's efforts in improving the ability of teachers to plan learning during the pandemic. (2) knowing the efforts of the principal in improving the ability of teachers to carry out learning during the pandemic. (3) knowing the efforts of school principals in improving the ability of teachers to evaluate learning during the pandemic. This research includes field research using a qualitative approach. In collecting data, this research uses interview, observation, and documentation methods as data collection techniques. And the technique chosen in data analysis is data reduction, data presentation and conclusion drawing. The results of this study are as follows: (1) the principal's efforts in planning learning, namely the existence of communication related to the obstacles encountered by the teacher, the socialization of changes in learning plans, monitoring, motivation, and academic supervision. (2) the efforts of the principal in implementing learning by teachers, namely by monitoring online learning, and forming a special team to control students who are less active in participating in online learning. (3) the principal's efforts in evaluating learning by teachers are by controlling all aspects related to supporting learning evaluation in order to facilitate the reporting of learning evaluation results, which are carried out online.